Prognostic analysis of children with tetralogy of Fallot through a small incision in the right axilla - Meng, Fanwei; Li, Jianchao; Liang, Weijie; Dong, Haoju; Li, Bing (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveCompare the clinical efficacy of a minimally invasive small incision in the right axilla vs. traditional median sternotomy in the surgical treatment of tetralogy of Fallot (TOF).MethodsA retrospective analysis was conducted on 330 infants and young children under the age of 3 who underwent radical surgery for tetralogy of Fallot between March 2022 and March 2024. Patients were categorized into two groups based on the surgical approach. To ensure the consistency of preoperative baseline data (weight, gender, age, O2 saturation, main pulmonary artery and pulmonary branches diameter, McGoon ratio) between the two groups, the propensity score matching method was applied for 1:1 matching, resulting in two cohorts of 228 cases. The minimally invasive group (n = 114) received surgery through a small incision in the right axilla, while the median sternotomy group (n = 114) underwent surgery via median sternotomy. Clinical parameters including demographic data (weight, gender, age, O2 saturation, main pulmonary artery and pulmonary branches diameter, McGoon ratio), cardiopulmonary bypass metrics (duration of bypass, aortic cross-clamp time), duration of mechanical ventilation, intensive care unit (ICU) stay, postoperative chest drainage volume within 24 h, pulmonary valve regurgitation, and complications (reintubation, peritoneal dialysis, reoperation, extracorporeal membrane oxygenation (ECMO) use, infection, and mortality) were collected for comparison between groups.ResultsNo statistically significant differences were observed between the two groups in 24 h chest drainage volume, mortality, reintubation, reoperation, ECMO use, and infection. However, the minimally invasive group showed significantly shorter ventilator duration and ICU stay and a reduced rate of peritoneal dialysis (all p < 0.05).ConclusionIn infants and children under 3 years old with TOF, surgical correction via a right axillary small incision achieves equivalent clinical outcomes to traditional median sternotomy, without increasing postoperative mortality or complication rates. In addition, the minimally invasive approach offers benefits of reduced surgical trauma and enhanced postoperative recovery.